2012
DOI: 10.1007/s11904-012-0140-x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of HIV and the Lung

Abstract: Antiretroviral therapy has improved longevity for HIV-infected persons, but long-term HIV infection is now complicated by increased rates of chronic medical conditions including pulmonary disorders. Chronic obstructive pulmonary disease, lung cancer, asthma, and pulmonary hypertension are becoming common comorbidities of HIV infection, and these diseases may develop as a result of HIV-related risk factors such as antiretroviral drug toxicities, colonization by infectious organisms, HIV viremia, immune activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 72 publications
0
39
0
Order By: Relevance
“…Much has been written about the occurrence of lung cancer in HIV-infected patients, with initial studies variously documenting it to be increased, decreased or the same in HIV-infected patients, compared to the general population [133][134][135][136][137][138][139][140][141]. More recently, several studies have suggested that there is indeed an increased incidence of lung cancer in HIV-infected patients, especially evident in the post-HAART era and associated with a poor outcome [134-138, 140, 141], with the adjusted risk ranging from 2.0 to 7.0 [18].…”
Section: Noninfective Pulmonary Conditions Lung Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…Much has been written about the occurrence of lung cancer in HIV-infected patients, with initial studies variously documenting it to be increased, decreased or the same in HIV-infected patients, compared to the general population [133][134][135][136][137][138][139][140][141]. More recently, several studies have suggested that there is indeed an increased incidence of lung cancer in HIV-infected patients, especially evident in the post-HAART era and associated with a poor outcome [134-138, 140, 141], with the adjusted risk ranging from 2.0 to 7.0 [18].…”
Section: Noninfective Pulmonary Conditions Lung Cancermentioning
confidence: 99%
“…oncogenic role of HIV and chronic immunosuppression) and increased susceptibility of HIV-infected persons to mutagens/carcinogens such as chronic inflammation-derived ROS and possibly antiretroviral agents [135,141]. However, the role of immunosuppression is unclear, with several studies suggesting involvement [136,139], while others have presented evidence to the contrary [138].…”
Section: Noninfective Pulmonary Conditions Lung Cancermentioning
confidence: 99%
See 3 more Smart Citations